Propuesta de estrategias para la conservación del sitio sagrado "Hatum pukyo", comunidad cuatro esquinas, Parroquia San Rafael de la Laguna - Cachimuel, Elsa S. (2018)
The present work aims to develop a proposal of strategies for the conservation of the sacred site "Hatun Pukyo", defining each of the main activities that serve as the basis for this proposal. The investigation was carried out in the community “Cuatro Esquinas” of the San Rafael de la Laguna, parish Otavalo canton, Imbabura province. For the development of the research we used the methods detailed in the introduction according to the field of study. The information was obtained through the design and application of interviews and surveys. In addition, the systematization of the results was carried out through the use of SPSS, version 24.